Suggestions to improve the quality of Chilean scientific journals: an application to forest science with Bosque - Salas, Christian (Bosque (Valdivia), 2008)
We comment on several topics of the Chilean scientific journals indexed in SciELO (Scientific Electronic Library Online) regarding: manuscript format, article format, review process, and other aspects that could improve their reputation and name and enhance recognition by international journals. Some of these topics are further developed, taking as example Bosque, the most important Chilean forestry journal and the only one that is indexed in SciELO. We suggest to increase the practice of accepting a wider range of manuscript computational formats, to establish an on-line system for submitting manuscripts (currently, 43.3% of the journals still require hardcopy submissions), to provide a template file for manuscripts to be available online, to streamline the categories of contributions accepted by journals, to establish the blind peer-review process (only 6% of the journals use it), and to have associate editors. Also, we suggest for Bosque to broaden the institutional diversity of reviewers.